Circulating Tumor DNA Detection in the Management of Anti-EGFR Therapy for Advanced Colorectal Cancer - Knebel, Franciele H.; Bettoni, Fabiana; da Fonseca, Leonardo G.; Camargo, Anamaria A.; Sabbaga, Jorge; Jardim, Denis L. (Frontiers in Oncology, 2019)
Background: anti-EGFR antibodies are a standard care for advanced KRAS-wild type colorectal cancers. Circulating tumor DNA (ctDNA) monitoring during therapy can detect emergence of KRAS mutant clones and early resistance to therapy. Case Presentation: we describe a 61-years-old man presenting a metastatic and recurrent rectal cancer treated with different chemotherapy regimens. His tumor was KRAS wild-type based on tissue analysis and he was treated sequentially with cetuximab-based chemotherapy, chemotherapy alone and panitumumab-based chemotherapy. We performed sequential analysis of ctDNA using droplet digital PCR (ddPCR) and a commercial assay designed for the detection of frequent KRAS mutations during his clinical follow-up. Prior to first cetuximab-based chemotherapy ctDNA analysis demonstrated absence of KRAS mutations. Emergence of KRAS mutations in ctDNA occurred approximately three months after treatment initiation and preceded clinical and imaging progression in about two months. Fractional abundance of KRAS mutation rapidly increased to 70.7% immediately before a chemotherapy alone regimen was initiated. Interestingly, KRAS mutation abundance decreased significantly during the first two months of chemotherapy, reaching a fractional abundance of 3.0%, despite minimal clinical benefit with this therapy. Re-challenge with a different anti-EGFR antibody was attempted as later line, but high levels of KRAS mutations in ctDNA before therapy correlated with an absence of clinical benefit. Conclusions: monitoring of resistance mutations in KRAS using ctDNA during treatment of KRAS wild-type advanced colorectal cancers can detect emergence of resistant clones prior to clinical progression. Dynamics of resistant clones may alter during periods on and off anti-EGFR antibodies, detecting window of opportunities for a re-challenge with these therapies.